Correlation of American Urological Association Symptom Index Domains with Uroflowmetric Peak Flow in Thai Patients with Suspected Benign Prostatic Hyperplasia - Sidaporn Chayochaichana; Julin Opanurak; Apirak Santingamkun; Supoj Ratchanon (Siriraj Medical Journal)
Objective: This study aimed to investigate the correlations between the obstructive and irritative domain scores of the total AUA-SI and the uroflowmetric peak flow rate (Qmax) in Thai patients suspected of having benign prostatic hyperplasia (BPH).